MRI imaging manifestations of severe toxic encephalopathy induced by excessive metoclopramide and multiple drug overdose: a case report - Liang, Pengfei; Tang, Yuncheng; Zhang, Xiaolin; Zhang, Li; Zhao, Juan; Tang, Haowen; Wu, Zeyu; Fang, Qiming; Fang, Zhicheng; Zhao, Zhiwen; Liu, Xuefang (Frontiers in Pharmacology, 2025)
ObjectiveTo investigate the clinical and MRI features of severe central nervous system injury caused by an extremely high dose of metoclopramide in combination with multiple drug overdoses, and to summarize treatment strategies and prognosis.MethodsWe report the clinical course of acute poisoning in a 36-year-old woman following a single oral intake of approximately 350 mg metoclopramide combined with adrenolizone and coenzyme Q10. Clinical manifestations, laboratory findings, imaging results (CT and MRI), and treatment interventions after admission were collected and analyzed. The possible pathological mechanisms were explored in conjunction with previous literature.ResultsUpon admission, the patient exhibited acute mental and behavioral disturbances, extrapyramidal symptoms, and impaired consciousness. Initial CT scans revealed no abnormalities. On the fourth day after admission, MRI demonstrated symmetrical patchy hyperintensities on T2WI/T2-FLAIR in the corpus callosum, bilateral corona radiata, and centrum semiovale white matter, along with hyperintensities on DWI and corresponding low ADC values, indicating cytotoxic edema consistent with toxic-metabolic encephalopathy. Following comprehensive multidisciplinary management-including early gastrointestinal decontamination, activated charcoal adsorption, HA380 hemoperfusion, hyperbaric oxygen therapy, neuroprotection, and symptomatic support-the patient was discharged on day 12. At the 3-month follow-up, no neurological sequelae were observed.ConclusionExtremely high-dose metoclopramide, particularly in combination with other drugs, can cause a characteristic symmetrical white matter injury pattern of toxic encephalopathy, with MRI findings offering high diagnostic value. Early recognition, prompt gastrointestinal decontamination, blood purification, and multi-target neuroprotective therapy can markedly improve prognosis.